LEGAL PROTECTION OF VULNERABLE GROUPS' RIGHTS IN GENERAL ELECTIONS - Sarbini, Dr.; Hartantien, Sinarianda Kurnia (jfpublisher, 2023)
A country is considered a democracy if the government regulations allow its citizens to participate in political activities to the greatest possible extent as a form of implementing democratic values. General elections are one of the main pillars to support a democratic political system. General elections are held to elect representatives of the people at the central and regional levels in order to obtain support from the public to achieve the country’s national goals which are held regularly in a certain period or period of time. General elections are a source of citizens’ aspirations in determining the leaders who will compete for their voices. It includes the fulfillment and protection of the rights of vulnerable groups. The approach used in this research is the juridical-normative approach, that is, legal research conducted by examining library materials or secondary materials as basic material to be researched by conducting a search for regulations and literature related to the problem being researched. According to The Indonesian National Human Rights Commission, there are groups of people whose voting rights are vulnerable to manipulation during elections. There are 16 vulnerable groups in the general election, such as: disabilities and people with mental disabilities (ODDM); prisoners; prison inmates, plantation and mining workers; migrant workers; domestic workers; frontier society; alienated tribal communities; the elderly; LGBTQ; PLHIV; refugees of social conflict/natural disasters; homeless; women; hospital patients and health workers; and novice voters.